PENGARUH PENGAWASAN TERHADAP KINERJA PEGAWAI PADA BADAN PENDAPATAN DAERAH KABUPATEN KUTAI TIMUR - Muhammad Sadli (ADMINISTRASI PUBLIK, 2018)
This study aims to determine whether there is a positive influence between Supervision with Employee Performance at the office of Regional Income Board of.East.Kutai.Regency.The population in this study is all employees who numbered as many as 20 people, considering the number taken relatively little then this research using census..method,..that..is..the..entire..population..made..as..respondents.Based on the description above, the analytical tool used in this research is Coefficient Correlation Product moment. From the calculation results indicate a significant influence between Supervision on Employee Performance at Regional Revenue Board of East Kutai Regency. This is based on the result of calculation which states that rhitung is bigger than rtabel that is 0,982> 0,561 for critical value at n = 20 with tariff significance = 0,01. For n = 20 then both variables have a..very..strong..relationship..level.After r arithmet obtained, then the authors conducted hypothesis testing using t test of the test results of this hypothesis, tcount of 22.058 while for keritis prices of ttable value is 2.552 which means that ttest> ttabel is 22.058> 2.552 with critical value n - 20 with a significance level of 0.01. Thus, It can be said that there is a very strong influence of the supervisory variable on employee performance variables at the Regional Income Board of East Kutai Regency.